The Use of Acellular Fish Skin Grafts in Diabetic Foot Ulcers Management – a Systematic Review ... - Hadikhosuma, Jessica; Lake, Maria Melita; Lewa, Anwar (Zenodo, 2023)
Background: Diabetic foot ulcer (DFU) healing and management continue to be a major challenge for patients and healthcare providers, resulting in a considerable socio-economic burden. Lower-limb amputation is a severe clinical condition of DFU due to the presence of a chronic unresponsive diabetic foot ulcer with a high risk of infection, which raises morbidity and mortality rates. Rapid wound healing is necessary to prevent amputation. A recent advance in the development of applicable xenografts was acellular fish skin (AFS) grafts harvested from the North Atlantic cod (Gadus morhua) act as skin substitute, have a substantial lipid profile, primarily composed of omega-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) which have been shown to result in faster wound epithelialization, provide barrier protection against bacteria and alter the inflammatory profile of wounds. Due to these beneficial wound-healing properties, acellular fish skin might represent an effective treatment ...